Museum worthy : Nazi art plunder in postwar Western Europe - Campbell, Elizabeth (Oxford University Press, 2024)
Art looting is commonly recognized as a central feature of Nazi expropriation, in both the Third Reich and occupied territories. After the war, the famed Monuments Men (and women) recovered several hundred thousand pieces from the Germans' makeshift repositories in churches, castles, and salt mines. Well publicized restitution cases, such as that of Gustav Klimt's luminous painting featured in the film Woman in Gold, illustrate the legacy of Nazi looting in the art world today. But what happened to looted art that was never returned to its rightful owners?